Hubungan Rasio Lingkar Pinggang Panggul dan Asupan Lemak dengan Risiko Kejadian Kardiovaskular pada Usia Produktif - Thahara, Adriani; Krisnawati, Ika (Fakultas Kedokteran Universitas Trisakti, 2023)
BACKGROUND Every year, cardiovascular disease (CVD) is the leading cause of death in the globe. The Framingham Risk Score forecasts the likelihood of cardiovascular diseases occurring within the next decade. Waist-to-Hip Ratio (WHR) is an anthropometric measurement representing abdominal fat and is regarded as superior to Body Mass Index (BMI) for predicting cardiovascular risk. Excessive fat intake will increase the risk of CVD. The purpose of this study is to determine the association between WHR and fat consumption and the risk of cardiovascular events in the productive age METHOD This cross-sectional observational study included 173 participants aged 30-64 at RW 12, Dutamas, Grogol Pertamburan, between September and November 2018. Using main data to determine the measures of WHR, BMI, data for FRS calculations, and 3x24-hour food recall interviews, data were collected using consecutive non-random sampling and non-random non-consecutive sampling. IBM SPSS 23 was utilized for the data analysis. RESULTS There were 62 male respondents and 111 female respondents. Both men and women are at risk of a high WHR measurement. However, men are more likely to be found with obesity in comparison to women. Both men and women presented a high fat intake of ³80% RDA. In the FRS test with WHR and fat intake, results show a p-value of <0.05 for men and women; meanwhile, the FRS test with BMI resulted in p> ​​0.05 for men and p<0.05 for women. CONCLUSION There was a relationship between the Waist-to-Hip Ratio (WHR) and fat intake with the risk of cardiovascular events.